A review of literature and code formulations for cracking in R/C members. (17th April 2018) - Lapi, Massimo; Orlando, Maurizio; Spinelli, Paolo
Abstract : Cracking in R/C members is a complex phenomenon characterized by high scattering, mainly affected by concrete in tensile zone. The aim of this paper is to evaluate the effectiveness of formulas for crack width prediction developed in last decades. First, an historical review of available literature models is presented and discussed. Second, the progress and missteps, which have characterized the development of international code provisions, are shown. Finally, a comprehensive comparison between predicted crack widths and experimental data is performed. Some formulas more than others provide mean values of crack width in good agreement with experimental data; nevertheless, predictions are always very scattered, as ratios between theoretical and experimental values have a coefficient of variation not lower than 30%. Results show that the prediction capacity does not necessarily increase as the cracking model is refined.